An efficient modified booth multiplier architecture - Razaidi, Hussin; Ali Yeon, Md Shakaff, Prof. Dr.; Norina, Idris; Zaliman, Sauli, Prof. Dr.; Rizalafande, Che Ismail; Afzan, Kamarudin (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/